PENGARUH INFLUENCER, BRAND IMAGE, PRICE, DAN PRODUCT QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE DENGAN LIFESTYLE SEBAGAI VARIABEL MODERATING - Yeni Septyani; Yuli Tri Cahyono (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of influencers, brand image, price, and product quality on purchase decisions in e-commerce with lifestyle as a moderating variable. This study uses a quantitative approach method with purposive sampling techniques. The type of data in this study is primary data with a collection method through questionnaires that have been made by researchers. The distribution of the questionnaire was carried out through a google form with a total of 102 respondents. The results of the study provide empirical evidence that influencers and product quality are influential, while brand image and price have no effect on purchase decisions in e-commerce. Furthermore, lifestyle is not able to moderate between influencers, price, and product quality, while lifestyle is able to moderate between brand image and purchase decisions in e-commerce